Location, but not defensive genotype, determines ectomycorrhizal community composition in Scots pine (Pinus sylvestris L.) seedlings. Issue 9 (27th March 2021) - Downie, Jim; Taylor, Andy F. S.; Iason, Glenn; Moore, Ben; Silvertown, Jonathan; Cavers, Stephen; Ennos, Richard
Abstract: For successful colonization of host roots, ectomycorrhizal (EM) fungi must overcome host defense systems, and defensive phenotypes have previously been shown to affect the community composition of EM fungi associated with hosts. Secondary metabolites, such as terpenes, form a core part of these defense systems, but it is not yet understood whether variation in these constitutive defenses can result in variation in the colonization of hosts by specific fungal species. We planted seedlings from twelve maternal families of Scots pine ( Pinus sylvestris ) of known terpene genotype reciprocally in the field in each of six sites. After 3 months, we characterized the mycorrhizal fungal community of each seedling using a combination of morphological categorization and molecular barcoding, and assessed the terpene chemodiversity for a subset of the seedlings. We examined whether parental genotype or terpene chemodiversity affected the diversity or composition of a seedling's mycorrhizal community. While we found that terpene chemodiversity was highly heritable, we found no evidence that parental defensive genotype or a seedling's terpene chemodiversity affected associations with EM fungi. Instead, we found that the location of seedlings, both within and among sites, was the only determinant of the diversity and makeup of EM communities. These results show that while EM community composition varies within Scotland at both large and small scales, variation in constitutive defensive compounds does not determine the EM communities of closely cohabiting pine seedlings. Patchy distributions of EM fungi at small scales may render any genetic variation in associations with different species unrealizable in field conditions. The case for selection on traits mediating associations with specific fungal species may thus be overstated, at least in seedlings. Abstract : Host defense genotype has previously been shown to affect associations with ectomycorrhizal (EM) fungi, but the extent to which secondary metabolites such as terpenes affect these associations is unknown. We conducted a reciprocal transplant field experiment to test the effect of varying terpene genotype on the EM community composition of individual seedlings and found that the only the location of a seedling affects community composition. Other processes affecting EM community composition at small scales, such as environmental preference and interspecific interactions, may thus preclude the expression of any effect of genotype in wild conditions.